Database and data communication network systems techniques and applications - Leondes, Cornelius T. (Amsterdam ; Boston : Academic Press, 2002)
Database and Data Communication Network Systems examines the utilization of the Internet and Local Area/Wide Area Networks in all areas of human endeavor. This three-volume set covers, among other topics, database systems, data compression, database architecture, data acquisition, asynchronous transfer mode (ATM) and the practical application of these technologies. The international collection of contributors was culled from exhaustive research of over 100,000 related archival and technical journals. This reference will be indispensable to engineering and computer science libraries, research libraries, and telecommunications, networking, and computer companies. It covers a diverse array of topics, including: * Techniques in emerging database system architectures * Techniques and applications in data mining * Object-oriented database systems * Data acquisition on the WWW during heavy client/server traffic periods * Information exploration on the WWW * Education and training in multimedia database systems * Data structure techniques in rapid prototyping and manufacturing * Wireless ATM in data networks for mobile systems * Applications in corporate finance * Scientific data visualization * Data compression and information retrieval * Techniques in medical systems, intensive care units.
v. 3. -- Information Data Acquisition on the World Wide Web During Heavy Client/Server Traffic Periods / Stathes Hadjiefthymiades and Drakoulis Martakos -- Information Exploration on the World Wide Web / Xindong Wu, Sameer Pradhan, Jian Chen, Troy Milner, and Jason Lowder -- Asynchronous Transfer Mode (ATM) Congestion Control in Communication and Data Network Systems / Saverio Mascolo and Mario Gerla -- Optimization Techniques in Connectionless (Wireless) Data Systems on ATM-Based ISDN Networks and their Applications / Rong-Hong Jan and I-Fei Tsai -- Integrating Databases, Data Communication, and Artificial Intelligence for Applications in Systems Monitoring and Safety Problems -- Paolo Salvaneschi and Marco Lazzari -- Reliable Data Flow in Network Systems in the Event of Failures / Wataru Kishimoto -- Techniques in Medical Systems Intensive Care Units / Bernardino Arcay, Carlos Dafonte, and Josβe. Taboada -- Wireless Asynchronous Transfer Mode (ATM) in Data Networks for Mobile Systems / C. Apostolas, G. Sfikas, and R. Tafazolli -- Supporting High-Speed Applications on Singaren ATM Network / Ngoh Lek-Heng and Li Hong-Yi.
Includes bibliographical references and index.
Keywords: Distributed databases; Computer network; Electronic books